(untitled) (Journal of Computational Mathematics, 2021)
By establishing the spectrum (matrix) function for the block Jacobi matrix, theorems of existence and uniqueness for the inverse problem and algorithms for its solution are obtained. The study takes into account all possible multiple-eigenvalue cases that are very difficult to deal with by other means.